Riemann-Liouville fractional-order pantograph differential equation constrained by nonlocal and weighted pantograph integral equations - Ahmed M. A. El-Sayed; Wagdy G. El-Sayed; Kheria M. O. Msaik; Hanaa R. Ebead (AIMS Mathematics)
In this research, we investigated the Riemann-Liouville fractional-order pantograph differential equation constrained by nonlocal and weighted pantograph integral constraints. We presented novel sufficient conditions for the uniqueness of the solution. Moreover, we analyzed the continuous dependence of the solution on some functions and parameters. Additionally, we proved the Hyers-Ulam stability of the problem. To demonstrate the applicability of our results, we included several examples. The present study was located in the space $ L_1[0, T] $. The techniques of Schauder's fixed point theorem and Kolmogorov's compactness criterion were the primary tools utilized in this work. These contributions offer a comprehensive framework for understanding the qualitative behavior of the fractional-order pantograph equation.